2021
DOI: 10.3390/chemosensors9020025
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots Fluorescence-Based Colorimetric Sensor for Sensitive Detection of Aluminum Ions with a Smartphone

Abstract: In this work, blue emission carbon dots (CDs) are synthesized in the one-pot solvothermal method using naringin as precursor. The CDs are used to develop a ratiometric fluorescence sensor for the sensitive analysis of Al3+ with a detection limit of 113.8 nM. A fluorescence emission peak at 500 nm gradually appears, whereas the original fluorescence peak at 420 nm gradually decreases upon the increase in the Al3+ concentration. More importantly, the obvious color change of the CDs probe from blue to green under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Figure S2a shows the XRD pattern of assynthesized O-CDs. The pattern indicates the presence of two relevant peaks around at (2θ =) 23 and 43°, representing the (002) and (100) planes, respectively-authenticating the presence of carbon [42,43]. This observation well coincides with the HRTEM observation for the formation of crystalline carbon at the core of O-CDs.…”
Section: Structural and Optical Properties Of The Hydrophilic O-cdssupporting
confidence: 82%
“…Figure S2a shows the XRD pattern of assynthesized O-CDs. The pattern indicates the presence of two relevant peaks around at (2θ =) 23 and 43°, representing the (002) and (100) planes, respectively-authenticating the presence of carbon [42,43]. This observation well coincides with the HRTEM observation for the formation of crystalline carbon at the core of O-CDs.…”
Section: Structural and Optical Properties Of The Hydrophilic O-cdssupporting
confidence: 82%
“…Because of its simple operation, rapid analysis, high selectivity and high sensitivity, it has attracted people's attention. 7…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the framework of the Q[n]s remained intact during this process, and the obtained Q[n]-CQDs (n = 7, 8) were shown to be potential multicolor biomarkers according to cytotoxicity tests and cell imaging results. 30 In this paper, based on the previous large particle sizes of Q [7] and Q [8], this study has used a single Q [6] with a smaller particle size as the precursor, and phenylenediamine (o-phenylenediamine, m-phenylenediamine, p-phenylenediamine) as the doping reagent. Through a onestep hydrothermal synthesis, N and O groups with hydrophilic and recognition functions on the surface of CQDs were directly obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorimetric sensors are devices whose fluorescence emission or absorption properties in the visible spectrum change upon interaction with specific targets. They are based on the variation of optical properties such as absorption and emission [20][21][22]. The operating principle of these sensors is relatively simple: they are used in combination with a light source, with a set wavelength and a detector.…”
Section: Introductionmentioning
confidence: 99%